Kajian Teoritis: Implementasi Metode Total Physical Response dalam Pembelajaran Bahasa Arab - Frananda, Angga; Sayuti, Muhammad; Azhar, Muhammad; Saputra, M. Ripani; Pasaribu, Mudiul Hayat (Shaut al Arabiyyah, 2026)
Learning Arabic requires a method that is fun and not boring so that the learning process goes well and the learning objectives can be achieved. This study aims to look at the implementation of learning Arabic using the total physical response (TPR) method because this method comes from the West. In carrying out his research, this study used descriptive qualitative methods. The steps that the authors carried out in this study were in the form of collecting data from several articles related to further research, the authors analyzed and described the results of these articles in the application of the total physical response method in language learning. Arab. The results of this study are in the form of a significant positive influence in learning Arabic using the total physical response method, especially in the mastery of mufradat. This research is expected to provide a scientific treasure, especially for educators in Arabic subjects.